AL-TA‘ASSUF PENGGUNAAN HAK PADA PUTUSAN MAHKAMAH KONSTITUSI NO. 46 TAHUN 2010 TENTANG ANAK LUAR NIKAH - Ahmad Arief (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2018)
Al-Ta'assuf's study is a concept that is very suitable for detecting any form of fraud and the use of personal or group rights. This proof is proven in the analysis of the Constitutional Court Decision, by describing and matching the indicators of al-ta‘assuf on the verdict. Theresults of the evidence state that the Constitutional Court Decision No. 46 is a form of al-ta‘assuf, stating the contents of the decision that disguises even the right of the wife and child committed in marriage that is legal and protected by religion and law. The Constitutional Court's verdict is very real contrary to the intention of al-Sya> ri ‘in everyorder and prohibition that is maslahat for all.